Modelling information flow for organisations delivering microsystems technology - Durugbo, Christopher (Cranfield University, 2011)
Motivated by recent growth and applications of microsystems technology (MST), companies within the MST domain are beginning to explore avenues for understanding, maintaining and improving information flow, within their organisations and to/from customers, with a view to enhancing delivery performance. Delivery for organisations is the flow of goods from sellers to buyers and a classic approach to understanding information flow is via the use of modelling techniques. Cont/d.